The fat controller: thomas & friends - Awdry, W. (Egmont London, 2008)
The Fat Controller, whose real name is Sir Topham Hatt, is the wise and sometimes stern leader of the North Western Railway on the Island of Sodor. He oversees all the engines and ensures that the railway runs smoothly. Though he can be strict, he is fair and always looks out for the best interests of his engines. He often gives the engines important tasks and challenges, helping them to learn and grow. Despite his stern exterior, he has a soft spot for each engine and celebrates their achievements.